Main Lobe Control of a Beam Tilting Antenna Array Laid on a Deformable Surface - Giulia Mansutti; Francesco Rigobello; Sajid M. Asif; Muhammad S. Khan; Antonio-D. Capobianco; Andrea Galtarossa (International Journal of Antennas and Propagation)
The projection method (PM) is a simple and low-cost pattern recovery technique that already proved its effectiveness in retrieving the radiation properties of different types of arrays that change shape in time. However, when dealing with deformable beam-tilting arrays, this method requires to compute new compensating phase shifts every time that the main lobe is steered, since these shifts depend on both the deformation geometry and the steering angle. This tight requirement causes additional signal processing and complicates the prediction of the array behavior, especially if the deformation geometry is not a priori known: this can be an issue since the PM is mainly used for simple and low-cost systems. In this letter, we propose a simplification of this technique for beam-tilting arrays that requires only basic signal processing. In fact the phase shifts that we use are the sum of two components: one can be directly extracted from strain sensor data that measure surface deformation and the other one can be precomputed according to basic antenna theory. The effectiveness of our approach has been tested on two antennas: a 4 × 4 array (trough full-wave simulations and measurements) and on an 8 × 8 array (trough full-wave simulations) placed on a doubly wedge-shaped surface with a beam tilt up to 40 degrees.